Sighting record listing, Iowa, 8/1/1999-11/28/1999, Bery Engebretsen - Engebretsen, Beryet al (1999)
An annotated list of birds sighted by Bery Engebretsen dated November 28, 1999. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1999. Epson - sheet feed